Evaluation and correction of smartphone-based fine time range measurements. (3rd July 2021) - Bai, Yuntian Brian; Kealy, Allison; Holden, Lucas
ABSTRACT: Wi-Fi-based positioning technology has been recognised as a useful and important technology for location-based service (LBS) accompanied by the rapid development and application of smartphones since the beginning of the 21 st century. However, no mature technology or method of Wi-Fi-based positioning had provided a satisfying output in the past 20 years, until recently, when the IEEE 802.11mc standard was released and hardware-supported in the market, in which a fine time measurement (FTM) protocol and multiple round-trip time (RTT) was used for more accurate and robust ranging without the received signal strength indicator (RSSI) involved. This paper provided an evaluation and ranging offset correction approach for Wi-Fi FTM based ranging. The characteristics of the ranging offset deviation errors are specifically examined through two well-designed evaluation tests. In addition, the offset deviation errors from a CompuLab WILD router and a Google access point (AP) are also compared. An average of 0.181 m accuracy was achieved after a typical offset correction process to the ranging estimates obtained from a complex surrounding environment with line-of-sight (LOS) condition. The research outcome will become a useful resource for implementing other algorithms such as machine learning and multi-lateration for our future research projects.